KEBIJAKAN PENGELOLAAN PULAU-PULAU KECIL TERLUAR INDONESIA DALAM MENGHAdAPI PERUBAHAN IKLIM GLOBAL - Sari, Diah Apriani Atika; Muslimah, Siti (Faculty of Law, Universitas Sebelas Maret, 2014)
Indonesia is an archipelago with thousands of islands scattered across the country. Among of these islands are small islands and outer islands of Indonesia territory which has sea border with neighboring countries. This research is a legal research. The source of data are secondary data. The research data are analyzed by qualitative approach. The results of this research show that the growing issue of climate change in the global world, cause the existence of small islands are in a high risk situation because of erosion and sea level rise. As a result, there will be pressure on the coastline so that some small islands are in the risk of losing some part of its land and even some islands are threatened to sink completely. Shoreline retreat in the outermost small islands could potentially result in a change in Indonesian maritime boundaries with neighboring countries and undermine Indonesia’s claim over the sea area. Moreover, Indonesia is still manage to establish some international agreements through bilateral diplomacy with neighboring countries, related to maritime boundaries with neighboring countries. This bilateral international agreement on border is absolutely necessary to strengthen claims over sea boundaries in Indonesia. Therefore, mitigation and adaptation strategies in deal with climate change issues are important to be integrated into the management policy of outermost small islands so that it will deliver a management concept that is resilience to climate change.